Wage Inequality and Wage Mobility in Turkey - Aysit Tansel; Basak Dalgic; Aytekin Güven (Institute for the Study of Labor (IZA), 2014)
This paper investigates wage inequality and wage mobility in Turkey using the Surveys on Income and Living Conditions (SILC). This is the first paper that explores wage mobility for Turkey. It differs from the existing literature by providing analyses of wage inequality and wage mobility over various socioeconomic groups such as gender, age, education and sector of economic activity. We first present an overview of the evolution of wages and wage inequality over the period 2005-2011. Next, we compute several measures of wage mobility and explore the link between wage inequality and wage mobility. Further, we compute the transition matrices which show movements of individuals across the wage distribution from one period to another and investigate the determinants of transition probabilities using a multinomial logit model. The results show that overall the real wages increased over the study period and wage inequality exhibits a slight increase. Wage inequality is one of the highest among the European Union (EU) countries. The wage mobility in Turkey is lower than what is observed in the European Union countries although it increases as time horizon expands. Wage mobility has an equalizing impact on the wage distribution, however; this impact is not substantial enough to overcome the high and persistent wage inequality in Turkey.
Keywords: D31; D63; J31; J60; 330; wage inequality; wage mobility; heterogeneity; Turkey